The effect of l-Citrulline in watermelon drink on cardiovascular endurance performance among ultimate frisbee athletes/ Dayang Nurul Hanadira Elpis - Hanadira Elpis, Dayang Nurul (2019)
Citrulline has been proposed as an ergogenic aid. Watermelon contains high in L-Citrulline concentration that show benefits to sport performance. Purpose:To investigate the effect of L-Citrulline in watermelon drink on cardiovascular endurance and in reducing muscle pain among ultimate frisbee athletes. Methods: This study involved a total of thirteen (N=13) of ultimate frisbee athletes from Universiti Teknologi MARA Sarawak (UiTM). Only 1 group that involved and using a convenience sampling method. Before the test, subjects were attending the familiarization phase three days before pre-test. The cardiovascular endurance performance was measured using Yo-Yo Intermittent Recovery Test 1, and the muscle pain rating scale was measured by using Visual Analog Scale (VAS). One-week after wash out period was given to the subjects as recovery time. Watermelon drinks was ingested to all subjects 1 hour before the post-test session and Visual Analog Scale (VAS) given after 24 hours. Results: Results ofthe current findings shows that there was an improvement on the effect of L-Citrulline in watermelon drink on cardiovascular endurance (13.53 ± 0.70) and reducing muscle pain (1.23 ± 0.443) with significant value (p=<0.05).